La Polynésie Française et l'Euro - Dropsy, Vincent (Victoria University of Wellington Law Review, 2007)
The legal status of French Polynesia has important implications for the local economy, in particular for its currency, the CFP franc. A resolution passed on January 19, 2006 by the Assembly of French Polynesia shows the political will to replace this currency by the euro. This article explains the institutional procedures necessary for a possible switch to the euro in French Polynesia, and analyses its economic advantages and drawbacks. The conclusion is that entering the euro zone would be in the best interests of French Polynesia.